Ginseng Panax and Its Impact on Mitigating the Negative Effects of Tin Chloride on Kidney Function and Serum Proteins in Male Rabbits - Salma Hamed; Marfoua Ali; Fayrouz Khaled (AlQalam Journal of Medical and Applied Sciences, 2025)
The existing investigation aimed to locate ginseng’s ability to resist the harmful effects of tin chloride "SnCl2" on the kidneys and serum proteins. Male rabbits were used in this investigation. The number of study groups was 4, each containing 5 rabbits, so the total number of rabbits used was 20. For twelve weeks, the animals underwent oral therapy per day. The experiment was designed as follows: The "Control group" (group 1) rabbits were given corn oil only. "Ginseng group" (group 2) rabbits were treated only with "100 mg/kg body weight" of ginseng. "Tin chloride (SnCl2) group" (group 3) rabbits were treated with "20 mg/kg body weight" of SnCl2 only. Finally, the "Ginseng + SnCl2 group" (group 4) rabbits were treated with SnCl2 and ginseng together. The outcomes displayed a substantial rise in the "Ginseng group" rabbit in the following serum parameters: "total protein (TP), albumin (A), and globulin (G)". A substantial "P<0.05" decrease of the "urea and creatinine." The exact opposite occurred in the "SnCl2 group", where serum proteins "TP, A, and G" decreased substantially, and "urea and creatinine" levels increased markedly. Ginseng minimizes the harmful effects of SnCl2 on all tested parameters, and this was demonstrated in the "Ginseng + SnCl2 group". In conclusion, Panax ginseng has an important role in reducing the harmful effects of SnCl2.